Predictors of utilization of public healthcare facilities in India: an empirical assessment. - Raina, Shahid Hamid; Dar, Khursheed Hussain; Hassan, Samir-ul; Ahmad, Masroor (Journal of Public Health: From Theory to Practice (2198-1833), 2024)
Aim: As the government of India has been undertaking various initiatives since 2005 (launch year of National Rural Health Mission) to increase the utilization of public healthcare facilities, it is very important to investigate the factors governing their utilization. Therefore, the purpose of this study was to explore the determinants of utilization of public healthcare facilities in India. Subject and methods: The data for the study were collected using a comprehensive structured interview schedule. Data were collected from 399 outpatients of district hospitals of the erstwhile state of Jammu and Kashmir, India. A logit model was used to study the variables determining the use of public healthcare facilities. Results: The results showed that distance and waiting time are negatively related to utilization, whereas satisfaction with hospital services and provision of free medicines are positively related and significantly increase the odds in favour of utilization of public hospitals. It was found that more than 60% of outpatients belonged to groups below the poverty line (BPL) and Antodaya Anna Yojna (AAY) families, but most of them had to spend out of pocket for medicines and diagnostic tests. Conclusion: The findings suggest that service delivery and provision of free medicines significantly increase the odds in favour of utilization whereas delayed services and distance decrease the odds in favour of utilization. Implications: The outcomes of this study are significant to achieve universal health coverage. Our study indicates that user fees should be abolished at least for economically disadvantaged patients, and the availability of medicines should be improved significantly to increase the utilization of public helathcare facilities as envisaged in National Health Policy, 2017.